Notes on Castniinae (Lepidoptera: Castniidae) of Margarita Island, Venezuela - González, Jorge; Ayala, José; Alnaúdez, José (Boletín del Centro de Investigaciones Biológicas, 1970)
Athis axaqua and Castnia invaria volitans are two new records of Castniinae (Lepidoptera) for Margarita Island, Nueva Esparta State, Venezuela. Only a few species of these large, Neotropical butterfly moths are present on Caribbean Islands. We reviewed specimens deposited in public and private collections, not only in Venezuela but worldwide, but found few Castniinae. It will not be surprising if other species of Castniinae are eventually found in Margarita, because host plants, such as bananas, pineapples and coconut palms, are now common throughout the island.